2023
DOI: 10.1063/5.0131358
|View full text |Cite
|
Sign up to set email alerts
|

Role of interface and valley-mixing scattering in a ferromagnetic silicene/superconductor junction

Abstract: We theoretically investigate the subgap transport in a ferromagnetic silicene/superconductor junction and highlight the role of the interface. It is demonstrated that the subgap conductance spectra for the continuous and discontinuous interface models are significantly different. In particular, the intravalley Andreev reflection (AR) may occur at the discontinuous interface, and then the subgap conductance will be remarkably enhanced when the silicene sheet is highly valley polarized. This novel AR resulted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…. In light of our theory, the photoinduced spin polarization is entirely different with that induced by the exchange energy in the ferromagnetic silicene [35,36]. The former is a result of different gap magnitudes for spin-up and spin-down electrons, while the latter is due to that the exchange field shifts normal Fermi level at Dirac points.…”
Section: The Photoinduced Spin Polarizationmentioning
confidence: 67%
“…. In light of our theory, the photoinduced spin polarization is entirely different with that induced by the exchange energy in the ferromagnetic silicene [35,36]. The former is a result of different gap magnitudes for spin-up and spin-down electrons, while the latter is due to that the exchange field shifts normal Fermi level at Dirac points.…”
Section: The Photoinduced Spin Polarizationmentioning
confidence: 67%
“…N Kσ > N K ′ σ , leading to the AF-induced valley polarization in silicene. This differs from the ferromagnetic exchange field or off-resonant light, which generates spin polarization in silicene [39,40]. When an electric field is also applied in the AF region, the spin degeneracy for the K and/or K ′ valleys is lifted, giving rise to the spin polarization in silicene.…”
Section: Band Structures and The Af-induced Valley Polarizationmentioning
confidence: 95%
“…In this paper, we propose a silicene-based AF/homo-or bulk-SC junction to study the valley-polarized subgap transport. The antiferromagnetic exchange field λ AF itself can induce valley polarization in silicene without the aid of an electric field, unlike the ferromagnetic exchange field or light field only generating spin polarization [39,40]. It is shown that, for a large λ AF , the Andreev-resonant peak at gap edge is supplanted by broadened features for the homo-SC model whereas by a sharp conductance dip for the bulk-SC model.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations